A Toolkit of Policy Options to Support Inclusive Green Growth - African Development Bank; Organisation for Economic Co-operation and Development; United Nations; World Bank (World Bank, Washington, DC, 2017)
In 2012, the Mexican Presidency of the G20 introduced inclusive green growth as a cross-cutting priority on the G20 development agenda. The second meeting of the G20 Development Working Group (DWG), hosted by the Government of the Republic of Korea, took place in Seoul the 19th and 20th of March 2012. As agreed during the first DWG meeting, this second meeting focused on the priorities for their presidency in the first half of 2012: infrastructure, food security and inclusive green growth (IGG). At its Seoul meeting, the DWG also agreed that IGG co-facilitators and relevant international organizations (IOs) should work together in 2012 to develop a nonprescriptive good practices guide/toolkit on enabling national policy frameworks for inclusive green growth to support countries who voluntarily wish to design and implement affordable and inclusive green growth policies, with the aim of achieving sustainable development and poverty alleviation. The toolkit is organized as follows. First, the necessity of applying the different tools in the context of a broad inclusive green growth strategy is stressed, and a harmonized framework combining approaches and tools identified by all four IOs is set forth. Second, the document offers an overview of key tools that can be mobilized to implement an inclusive green growth strategy. Quick technical descriptions of these tools are offered along with suggested sources for further details. Finally, capacity building and knowledge sharing initiatives are presented, with the Green Growth Knowledge Platform (GGKP) highlighted as a powerful collaborative tool to advance policies for inclusive green economies.